Characterization of dyestuffs and metals from selected 16-17th-century ottoman silk brocades by RP-HPLC-DAD and FESEM-EDX (Article) - Karadaǧ, Recep (My University, 2015)
In this study, the analysis of dyestuff and metal thread samples present in the 16-17th-century Ottoman silk textile samples were performed by HPLC-DAD (high-performance liquid chromatography coupled with diode array detection) and FESEM-EDX (field emission scanning electron microscopy with energy dispersion spectroscopy). HPLC-DAD was used for the identification of dyestuffs in different plants and insects such as weld, dyer's oak, walloon oak, woad, indigo, madder, young fustic, and cochineal. Silk yarns with yellow, blue, orange, brown, red, and green colors were selected for the analysis. One of the most useful procedures for fast and simple determination of specific metals of interest is FESEM-EDX. This is a simple method that provides information on chemical composition of sample surfaces and chemical analysis of metal threads. © 2015 Copyright Taylor & Francis Group, LLC.
Keywords: cultural heritage; dyestuff; FESEM-EDX; HPLC-DAD; metal thread; Ottoman silk brocade